(untitled) (Research, Society and Development, 2020)
The community of aquatic insects is extremely abundant and diverse in neotropical streams, presenting great importance for studies of streams in the present day. Therefore, the present study has the objective of analyzing and identifying the aquatic insect community of a section of the Tijuca - Tijuca Forest (Rio de Janeiro, RJ). The sampling was performed in 2017 using a surber (30x30 cm, 250 μm mesh) with which 12 samples were collected from 3 habitats (litter, rock and sand) and 2 distinct mesohabitats (pool and riffle). A total of 1.836 aquatic insects were found, with the litter substrate being the most abundant (1.084), followed by sand (434) and stone (318). Therefore, the study concluded that there is great abundance and variety of aquatic insects present in the stretch of the Tijuca River, where the substrate type and the mesohabitat are determinant to understand the distribution of the individuals along the water body.